Tyrosine Kinase Inhibitors Reduce NMDA NR1 Subunit Expression, Nuclear Translocation, and Behavioral Pain Measures in Experimental Arthritis - Westlund, Karin N.; Lu, Ying; Zhang, Liping; Pappas, Todd C.; Zhang, Wen-Ru; Taglialatela, Giulio; McIlwrath, Sabrina L.; McNearney, Terry A. (Frontiers in Physiology, 2020)
In the lumbar spinal cord dorsal horn, release of afferent nerve glutamate activates the neurons that relay information about injury pain. Here we examined the effects of protein tyrosine kinase (PTK) inhibition on NMDA receptor NR1 subunit protein expression and subcellular localization in an acute experimental arthritis model. PTK inhibitors genistein and lavendustin A reduced cellular histological translocation of NMDA NR1 in the spinal cord occurring after the inflammatory insult and the nociceptive behavioral responses to heat. The PTK inhibitors were administered into lumbar spinal cord by microdialysis, and secondary heat hyperalgesia was determined using the Hargreaves test. NMDA NR1 cellular protein expression and nuclear translocation were determined by immunocytochemical localization with light and electron microscopy, as well as with Western blot analysis utilizing both C- and N-terminal antibodies. Genistein and lavendustin A (but not inactive lavendustin B or diadzein) effectively reduced (i) pain related behavior, (ii) NMDA NR1 subunit expression increases in spinal cord, and (iii) the shift of NR1 from a cell membrane to a nuclear localization. Genistein pre-treatment reduced these events that occur in vivo within 4 hours after inflammatory insult to the knee joint with kaolin and carrageenan (k/c). Cycloheximide reduced glutamate activated upregulation of NR1 content confirming synthesis of new protein in response to the inflammatory insult. In addition to this in vivo data, genistein or staurosporin inhibited upregulation of NMDA NR1 protein and nuclear translocation in vitro after treatment of human neuroblastoma clonal cell cultures (SH-SY5Y) with glutamate or NMDA (4 h). These studies provide evidence that inflammatory activation of peripheral nerves initiates increase in NMDA NR1 in the spinal cord coincident with development of pain related behaviors through glutamate non-receptor, protein tyrosine kinase dependent cascades.